1984
DOI: 10.1007/bf02101981
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of repetitive DNA sequences in deer species studied by Southern blot transfer

Abstract: The Cervidae show one of the largest variations in chromosome number found within a mammalian family. The five species of the deer family which are the subject of this study vary in chromosome number from 2n = 70 to 2n = 6. Digestion with the restriction enzymes EcoRI, HpaII, HaeIII and MspI reveals that there is a series of highly repetitive sequences forming similar band patterns in the different species. To obtain information on the degree of homology among these conserved sequences we isolated a HpaII rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Moose and caribou most likely have descended from lineages which did not give rise to the Odocoileus or Mazama species. Lima de Faria et al (1984) found that Alces and Rangifer were more homologous than Rangifer and other cervids, and perhaps sequence information from the Pudu (Pudu), the Hippocamelus (Heumul), and the Ozotoceros (Pampas deer) will shed some light on the relationship of these species. Estimated times of divergence for assessing the relationship among the Odocoileinae is not helpful because sequences have diverged more than 10%, which produces a large variation in the estimation.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moose and caribou most likely have descended from lineages which did not give rise to the Odocoileus or Mazama species. Lima de Faria et al (1984) found that Alces and Rangifer were more homologous than Rangifer and other cervids, and perhaps sequence information from the Pudu (Pudu), the Hippocamelus (Heumul), and the Ozotoceros (Pampas deer) will shed some light on the relationship of these species. Estimated times of divergence for assessing the relationship among the Odocoileinae is not helpful because sequences have diverged more than 10%, which produces a large variation in the estimation.…”
Section: Resultsmentioning
confidence: 96%
“…Researchers began using protein electrophoresis (Bonnel and Selander, 1973;Cameron and Vyse, 1978;Ryman et al, 1977) but found little variation among large mammals, and in more recent years, the focus has moved to comparisons of DNA. Genetic markers have been used to separate the order Artiodactyla into suborders (Modi et al, 1996), the suborder Ruminantia into superfamilies Bovoidea and Cervoidea (Comincini et al, 1996), and family Cervidae into subfamilies (Miyamoto et al, 1990;Lima de Faria et al, 1984;Comincini et al, 1996;Cronin et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cervid species, a major centromeric satellite DNA family appears to be predominantly organized into monomer sizes of 0.8 kb in the Indian and Chinese muntjac genomes (Bogenberger et al 1985, Yu et al 1986, Lin et al 1991, 1 kb in the reindeer (Lima-de-Faria et al 1984, Lee et al 1994 and 2 kb in the European roe deer (Scherthan 1991). The first two cervid centromeric satellite DNA monomers to be cloned (both 0.8 kb in length and from the Indian muntjac genome) demonstrated the presence of internal 31-bp, tandemly organized subrepeats that were homologous to the 31-bp subrepeat found in bovine 1.715 satellite DNA.…”
Section: Introductionmentioning
confidence: 99%
“…1981). Repetitive sequence satellite DNA is highly conserved, not only between the two muntjac species but in several other Artiodactvlae as well (Lima-de-Faria et al, 1984Bogenberger, 1985;Y uetal., 1986;Scherthanetal.. 1987;Scherthan, 1991). There appears to be a reduced amount of mid-and low-repetitive DNA in M. muntiacus, which may have evolved by repeated centric fusions and tandem transloca tions of the M. reevesi chromosomes, mediated by homologous recombination and subsequent loss of moderately complex repetitive DNA (Schmidtke et al.…”
mentioning
confidence: 99%